AKUTNE.CZ algorithms and SEPSIS-Q scenarios as interactive tools for problem based learning sessions in medical education - Štourač, Petr; Harazim, Hana; Schwarz, Daniel; Křikava, Ivo; Komenda, Martin; Štoudek, Roman; Smékalová, Olga; Kosinová, Martina; Hůlek, Richard; Maláska, Jan; Šustr, Radim; Šnábl, Ivo; et al. (Mefanet journal, 2013)
This paper describes the interactive tools of the AKUTNE.CZ (part of MEFANET) and SEPSIS-Q portals for Problem Based Learning (PBL) sessions in medical education. The portals aim to be a comprehensive source of information and educational materials, covering all aspects of acute medicine for undergraduate medical students and health professionals. Our focus is mainly on simulation-based tools for teaching and learning algorithms in acute patient care, the backbone of the AKUTNE.CZ and SEPSIS-Q portals. Over the last five years, more than 30 interactive algorithms in the Czech and English languages (http:// www.akutne.eu) have been devel¨oped and published online, allowing users to test and improve their knowledge and skills in the field of acute medicine. Additionally, we have created six SEPSIS-Q interactive scenarios in the Czech version. The peerreviewed algorithms were used for conducting PBL-like sessions in General Medicine (First Aid, Anaesthesiology and Pain Management, Emergency Medicine) and in Nursing (Obstetric Analgesia and Anaesthesia for Midwives, Intensive Care Medicine). The interactive scenarios serve to demonstrate interesting cases, with preference for Intensive Care Medicine sessions in General Medicine and Nursing.
Keywords: algoritmy; Emergency Medicine; Problem-Based Learning; Computer-Assisted Instruction; studium ošetřovatelství bakalářské; sepse; urgentní lékařství; Humans; Education, Nursing, Baccalaureate; problémově orientovaná výuka; lidé; Algorithms; studium lékařství pregraduální; Education, Medical, Undergraduate; Sepsis; počítačem řízená výuka